2019
DOI: 10.1177/2158244019853467
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Entrepreneurial Intention: Testing an Integrated Model of SDT and TPB

Abstract: The purpose of this study is to test an integrated entrepreneurial motivation and intention model based on self-determination theory (SDT) and the theory of planned behavior (TPB). Particularly, it aims at testing the direct and indirect effects of the basic psychological needs satisfaction of SDT, that is, autonomy, competence, and relatedness on entrepreneurial intention through the TPB attitudinal factors, that is, attitude toward entrepreneurship, subjective norms, and perceived behavioral control. A sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 94 publications
12
96
3
4
Order By: Relevance
“…In this way, it joins the growing literature that explores how basic psychological needs act as motivational drives that positively influence one’s future, including career choice [ 34 ]. Our findings have shown that satisfaction of needs is positively related to entrepreneurial intentions in support of the consensus that, to be successful, an entrepreneur must express and use various skills, including those aimed at satisfying his needs and at achieving your own well-being in general [ 82 , 131 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this way, it joins the growing literature that explores how basic psychological needs act as motivational drives that positively influence one’s future, including career choice [ 34 ]. Our findings have shown that satisfaction of needs is positively related to entrepreneurial intentions in support of the consensus that, to be successful, an entrepreneur must express and use various skills, including those aimed at satisfying his needs and at achieving your own well-being in general [ 82 , 131 ].…”
Section: Discussionsupporting
confidence: 77%
“…In an interesting study with university students in Yemen, Al-Jubari [ 82 ] tested the influence of satisfying the basic psychological needs of SDT on business intention through the factors of the theory of planned behavior. The results of the study support the theoretical integration of the model, in which the satisfaction of basic psychological needs has a positive effect on the attitude towards entrepreneurship, subjective norms, and perceived behavioral control and these, in turn, have a positive effect in the entrepreneurial intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A number of studies agreed that TPB predicted different behaviors via external variables and antecedents (e.g., Chen and Hung, 2016;Paul et al, 2016;Hsu et al, 2017;Al-Jubari, 2019;Sun et al, 2019;Hoque and Hossan, 2020;Parash et al, 2020;Si et al, 2020;Uzun and Kilis, 2020). A meta-analysis conducted by Hagger et al (2002) confirmed that the three aforesaid factors can be used to predict behavioral intentions and behavior.…”
Section: Theory Of Planned Behaviormentioning
confidence: 87%
“…Among various theories employed to study EI among students, the theory of planned behavior (TPB) has been extensively used (Gird & Bagraim, 2008;Karimi et al, 2016;Kautonen et al, 2015;Maresch et al, 2016;Miranda et al, 2017). Researchers have sought to understand EI through other theoretical models and by integrating TPB with other theories as well (Al-Jubari, 2019;Kallas, 2019). However, studies related to EI in the technical education context are few, especially in developing countries.…”
Section: Research-article20202020mentioning
confidence: 99%